Taking the VITALS to Interrupt Microaggressions - Valencia P. Walker; La'Mayah Hodges; Monica Perkins; Myung Sim; Christina Harris (Association of American Medical Colleges, 2022)
Introduction Microaggressions are subtle statements or actions that reinforce stereotypes. Medical students, residents, and faculty report experiences of microaggressions, with higher incidences among women and marginalized groups. An educational tool utilizing the acronym VITALS (validate, inquire, take time, assume, leave opportunities, speak up) provided a framework for processing and addressing microaggressions encountered in the academic health center environment. Methods We developed a 60-minute workshop designed to raise awareness of microaggressions encountered by medical students and trainees. The workshop consisted of a didactic presentation and multiple interactive exercises shared in small- and large-group formats. Participants also completed pre- and postsurvey instruments to assess changes in their knowledge and attitudes about promoting an environment that prevents microaggressions from occurring. Results There were 176 participants who completed our workshop. In comparing anonymized pre- and postworkshop responses submitted by attendees, an increase in recognition of one's own potential stereotypical beliefs about social identity groups was observed. Participants also expressed a greater sense of empowerment to foster mutual respect in health care settings. After completing the workshop, attendees indicated a greater likelihood to engage in difficult conversations, including responding to microaggressions, which both peers and superiors encountered in both academic and clinical environments. Discussion The workshop provided an interactive format for medical students and trainees to gain awareness, knowledge, and tools for addressing microaggressions encountered in health care settings.